Top 10 for Boys 2014 - Terry, Paul (London Hamlyn, 2013)
"A collision of the most exciting facts on Earth! From the 10 greatest superhero movies and 10 most successful video games, to the 10 biggest sharks and 10 fastest jets, this book will simply amaze you! Plus, it's interactive - you and your friends get to have your say about what you think should be at the top slots!"--Page 4 of cover.
Includes Colored Illustrations
Keywords: Curiosities and wonders